2021
DOI: 10.1177/14614448211000666
|View full text |Cite
|
Sign up to set email alerts
|

“What an idiot!” – How the appraisal of the writer of an uncivil comment impacts discussion behavior

Abstract: Despite incivility in online discussions being linked to various negative effects, less is known about the mechanisms of how incivility works. So far, explanations by social perception have been neglected. Therefore, drawing on the multiple inference model, this study employs an attribution theoretical approach to examine whether the motives and traits that people attribute to senders of uncivil or opposing comments affect their intentions to join a discussion. Employing a 2 (incivility vs. no incivility) × 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This pattern is very likely to contribute to conflicts when it comes to cross-cutting discussions since people seemingly pay more attention to an individual's (different) stance than to the prevailing communication norm. Thus, adding to previous research on the effects of disagreement and incivility (e.g., Chen & Lu, 2017;Gervais, 2017;Kluck & Krämer, 2021), our results indicate that people focus rather on person factors like the stance of commenters than on the social context.…”
Section: The Impact Of Descriptive Norms and Disagreementsupporting
confidence: 68%
See 4 more Smart Citations
“…This pattern is very likely to contribute to conflicts when it comes to cross-cutting discussions since people seemingly pay more attention to an individual's (different) stance than to the prevailing communication norm. Thus, adding to previous research on the effects of disagreement and incivility (e.g., Chen & Lu, 2017;Gervais, 2017;Kluck & Krämer, 2021), our results indicate that people focus rather on person factors like the stance of commenters than on the social context.…”
Section: The Impact Of Descriptive Norms and Disagreementsupporting
confidence: 68%
“…Consequently, people should appraise uncivil discussion behavior preceded by other uncivil comments as less aggressively motivated than uncivil discussion behavior that is preceded by comments, not including incivility. Supporting this idea, as discussed earlier, it was found that inducing aggressive behavior is appraised as more negative than reactive aggressive behavior (Reeder et al, 2002) and people attribute more aggressive discussion motives to individuals who comment in an uncivil manner compared to those who comment civilly (Kluck & Krämer, 2021). Yet, in the context of online discussions, it has not been investigated how the attribution of discussion motives for uncivil commenting differs depending on the amount of incivility in other comments.…”
Section: Impact Of Preceding Commentsmentioning
confidence: 60%
See 3 more Smart Citations